Efeitos da meta-clorofenilpiperazina (mCPP) sobre a aprendizagem reversa em ratos: implementação do teste e exploração de diferenças entre machos e fêmeas - Leite, Erinete da Silva (2022)
Several mental disorders are known for behavioral rigidity, especially ObsessiveCompulsive Disorder (OCD), which is associated with dysfunctions in the prefrontal cortices and resistance to reconditioning when environmental rules are changed (reversal learning). Rats treated with meta-chlorophenylpiperazine (mCPP) are used as an animal model for OCD, showing changes such as increased anxiety and compulsive behaviors. Little is known, however, about the effects of mCPP in females and behavioral flexibility. The present study aimed to implement the reversal learning test and apply it to rats treated with mCPP, verifying potential performance differences in relation to the model and between sexes. 145 adult Wistar rats (10-12 weeks old, 73 males and 72 females) were conditioned in a T-maze and subsequently reconditioned for the reversal learning test. In experiment 1, males and females were compared to each other. Males and females learned alike about the position of food in the maze, progressively decreasing omissions, mistakes made, and the time to reach the food. Differences between sexes were observed only in the reversal learning phase, with a greater number of errors made by females in these sessions, indicating less behavioral flexibility to decouple the behavior from a previously learned and well-established rule. In experiment 2, mCPP or saline administrations occurred 20 min before each session. 2 mg/Kg of mCPP produced an increase in omissions and reaction time in females, both in learning and in reversal learning, in addition to a longer reaction time for males only in reversal learning. These results suggest a more prominent motor and/or motivational effect of mCPP in females even more important than the induction of OCD-related behavioral inflexibility.